GRADO DE CONOCIMIENTO DEL PERSONAL ASISTENCIAL, SOBRE LA RESPUESTA ANTE EMERGENCIAS Y DESASTRES NATURALES EN EL CENTRO DE SALUD SUNAMPE-CHINCHA, DICIEMBRE 2016 - CCASA SUAREZ, WALTER GUSTAVO (2016)
The present study raises as one of the main objectives to establish and quantify the level of information, based on the knowledge that the assistance personnel of the Sunampe health center have, in the face of situations called emergencies or disasters, all this during the period 2016. This The study is considered to have quantitative characteristics of a descriptive nature and of a transversal time. The population established for the sample was taken by 50 healthcare collaborators from the Sunampe health center, located in the province of Chincha. For the data collection, various instruments are used, such as a questionnaire, as well as a pilot test that is established prior to the application of the instruments. The degree of reliability of the questionnaire according to Cronbach's alpha is 0.932. Therefore, it is established that this degree of reliability is high since it is much closer to the unit. Among the results, it was established that a total of 54% of the studied personnel has a regular knowledge of the situations called emergencies and disasters, in addition, 54% of all the inhabitants present a good knowledge about the concepts that are established within the emergency situations. In addition, it is evident that all the assistance personnel in our research, 48% have adequate knowledge for the phase prior to the emergency and disaster situations, however, for the stage of during the disaster only 68% obtained regular acquaintance. Finally, for the after phase it was established that only 44% of the respondents presented an inadequate level of knowledge. It is concluded that the regular knowledge of the majority of the workers is not a guarantee for the effectiveness of the work team in the face of an emergency or disaster situation. Key words: Emergencies, natural disasters, relief workers.